Factors influencing presenteeism: The role of individual characteristics, job demands, and job insecurity in the workplace - Salsabil, Salwa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Presenteeism affects both the quality and quantity of work, leading to decreased concentration, reduced performance, lower productivity, and increased costs, ultimately impacting organizational efficiency. This study explores the relationship between individual characteristics, job demands, and job insecurity with presenteeism among employees at PT X in 2024. Method: This research employs a cross-sectional study design, with data analyzed using the chi-square test. A purposive sampling method was used to select 90 employees from PT X. The study utilized the Stanford Presenteeism Scale-6 questionnaire, the Job Demands-Resources (JDR) model, and the job insecurity scale developed by Hellgren. Results: The findings of the study reveal that a significant number of employees displayed high levels of presenteeism. Specifically, 70 employees were identified as exhibiting this behavior, which represents 77.8% of the total employee population. This indicates that a large proportion of the workforce is physically present at work but not fully engaged or productive. Conclusion: The study concludes that job insecurity and gender are significantly associated with presenteeism. To address this issue, companies should enhance communication regarding policies, job status, and future organizational direction. Novelty/Originality of this Study: This study uniquely underscores the role of job insecurity and gender in presenteeism, offering valuable insights into workplace productivity. The findings suggest targeted interventions focusing on job security and transparent communication to mitigate presenteeism and improve overall employee well-being.